Ответы и объяснения

2014-04-14T04:52:06+00:00
2(3х-5)-3(1-2х)-4х=-3
6х-10-3+6х-4х=-3
8х-13=-3
8х=-3+13
8х=10
х=10/8=1 2/8=1 1/4=1,25
2014-04-14T04:55:43+00:00
2(3х-5)-3(1-2х)-4х=-3                                                                                                   6х-10-3+6х-4х=-3                                                                                                      6х+6х-4х=10+3-3                                                                                                     8х=10                                                                                                                       х=10:8                                                                                                                     х =1.(2)